Our masks in the virtual world: relationship between virtual identity, self-esteem and internet addiction - Kabar, Pelin (Journal of Dependence, 2023)
Objective: This research aims to explore the link between virtual identity, self-esteem, and internet addiction levels, shedding light on the impact of internet addiction on mental health.Method: The study's sample consisted of 300 volunteers, including 145 women and 155 men aged 18-60. Participants completed a demographic information form, the Social Comparison Scale, the Internet Addiction Scale Short Form, and the Virtual Identity Scale.Results: A significant negative correlation was observed between self-esteem and internet addiction (r= -.387, p< .01), and between virtual identity and internet addiction (r= -.429, p< .01). Marital status did not significantly affect selfesteem and virtual identity scores (f=1.59, p> .005; f=1.86, p> .005). However, marital status influenced internet addiction levels, with single individuals showing higher addiction levels than married ones (f=5.53, p< .005).Conclusion: Virtual identity and low self-esteem appear to contribute to internet addiction. Enhancing self-esteem may decrease the reliance on virtual identity and lower internet addiction risks, potentially alleviating other psychological issues.
Keywords: Internet addiction disorder; virtual identity; self-esteem